Problematika Film Alih Media: Dari Transformasi Hingga Kontroversi - Saidi, Acep Iwan; Puspitasari, Dyah Gayatri (Panggung, 2020)
ABSTRACT This article contains a study of film adaptation from a literature media (novel) into audio-visual media (film). This research is a case study of Perempuan Berkalung Sorban film by Hanung Bramantyo, which was adapted from a novel with the same title that was written by Abidah el-Khalieqy. By combining a text analysis method from Thomas Leittch, Mathew T. Jones’ film adaptation theory and the result of interview to confirm the text analysis, this research produced some interesting findings. The research verified that the adaptation’s process does not merely focus on technical issue in media adaptation (from novel to film), but also focuses on another aspects that will involve the audience i.e. a fact that text and dialogue become references that will be appreciated by audience. As a result, there were excessive distortions and deviations on the text that were created by the film maker caused a bias interpretation. Audiences no longer interpreted the film as a visual text objectively. Instead, they would think about certain prejudice against the film maker. In film adaptation, certain tendencies of film maker are easy to be predicted by audience. This fact has caused film adaptation becomes controversial easily. Keywords: Media Adaptation, Transformation, Opposition, Controversy ABSTRAK Artikel ini berisi kajian tentang alih media, yakni dari media verbal sastra (novel) kemedia visual film. Kajian ini berupa studi kasus terhadap film Perempuan Berkalung Sorban karya Hanung Bramantyo, yang merupakan adaptasi dari novel dengan judul sama karya Abidah el-Khalieqy. Dengan menggunakan metode gabungan, yakni analisis teks yang berdasar pada teori adaptasi film dari Thomas Leittch, Mathew T. Jones, dan wawancara tertulis untuk mengkonfirmasi analisis teks tadi, kajian ini menemukan hal menarik, yakni alih media bukan sekedar persoalan teknis pemindahan media, melainkan juga pemindahan yang menimbulkan efek-efek tertentu bagi penonton. Apresiasi penonton dilandasi kesadaran bahwa terdapat teks lain yang menjadi rujukan film bersangkutan. Akibatnya, distorsi dan deviasi yang terlalu jauh yang dilakukan sutradara atas teks sumber berpotensi mengakibatkan bias pemahaman. Penonton tidak lagi memaknai film sebagai teks visual secara objektif, tetapi juga dibarengi praduga-praduga tertentu terhadap sutradara. Pada genre film alih media, tendensi tertentu dari sutradara mudah dibaca penonton. Fakta ini mengakibatkan film sangat rentan menimbulkan kontroversi. Kata Kunci: alih media, transformasi, oposisi, kontroversi